Uporaba vodnega curka za postopno preoblikovanje pločevine - Junkar, Mihael (Strojniški vestnik, 2004)
High-speed jetting technology has developed quickly over the past few decades.Since its first introduction in the early 1970s the number of applications has rapidly increased. Of the high-speed jet-based processes, cutting with an abrasive water jet (AWJ) is the most common. In this process, hard abrasive particles, which are accelerated by a high-speed water jet (WJ),can erode practically any known material. On the other hand, a plain WJ is used mostly for cutting softer materials, cleaning, surface preparation, applications in medicine and food processing. Recently, WJs have been used in forming, mostly as a tool for surface peening, but some research has shown great potential for a WJ as a tool for incremental sheet-metal forming (ISMF). In this study we analyzed the possibility to apply a high-speed WJ as a tool for ISMF. The importance of process parameters such as water pressure and volume flow were determined, and the most appropriate water-nozzle geometry was defined as well. A case study is included, where a simple geometry was incrementally formed by a WJ in 0.5-mm-thick aluminum-alloy plate. Compared to ISMF with a rigid tool, the proposed technology is more environmentally friendly, since no lubrication is required, and from our firstinvestigation it seems that the formability is increased as well.
Keywords: preoblikovanje pločevine; postopki nekonvencionalni; izdelava prototipov hitra; curek vodni; pločevina; preoblikovanje; vodni curek